Non‐targeted volatile profiles for the classification of the botanical origin of Chinese honey by solid‐phase microextraction and gas chromatography–mass spectrometry combined with chemometrics. Issue 22 (10th October 2017) - Chen, Hui; Jin, Linghe; Fan, Chunlin; Wang, Wenwen
Abstract: A potential method for the discrimination and prediction of honey samples of various botanical origins was developed based on the non‐targeted volatile profiles obtained by solid‐phase microextraction with gas chromatography and mass spectrometry combined with chemometrics. The blind analysis of non‐targeted volatile profiles was carried out using solid‐phase microextraction with gas chromatography and mass spectrometry for 87 authentic honey samples from four botanical origins (acacia, linden, vitex, and rape). The number of variables was reduced from 2734 to 70 by using a series of filters. Based on the optimized 70 variables, 79.12% of the variance was explained by the first four principal components. Partial least squares discriminant analysis, naïve Bayes analysis, and back‐propagation artificial neural network were used to develop the classification and prediction models. The 100% accuracy revealed a perfect classification of the botanical origins. In addition, the reliability and practicability of the models were validated by an independent set of additional 20 authentic honey samples. All 20 samples were accurately classified. The confidence measures indicated that the performance of the naïve Bayes model was better than the other two models. Finally, the characteristic volatile compounds of linden honey were tentatively identified. The proposed method is reliable and accurate for the classification of honey of various botanical origins.